¿Qué es un problema matemático? percepciones en la enseñanza media costarricense - Alfaro Carvajal, Cristian (2008)
Teaching mathematics through problem solving is one of the main lines of investigation in Mathematics Education. This pedagogical strategy requires defining appropriately the concept “mathematical problem” and the meaning of its use in the classroom. In this work some results are presented, which were obtained by a survey to students and teachers of High School in Costa Rica.